Menejerial Marketing Melalui Sosial Media Sebagai Strategi Pemasaran bagi UMKM di Desa Rejosopinggir Jombang - Anggun Wulandari; Asiyah Lu’lu’ul Husna; Suci Prihatiningtyas (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2024)
The development of digital technology allows MSME actors to market their products online and make transactions through the online banking system as well. Social media is the easiest digital marketing to use. Marketing activities carried out by MSMEs in the village of Rejosopinggir Jombang by visiting shops/ restaurants/ markets. In addition, MSMEs only produce their products after there is an order. Marketing activities are still Jombang area and its surroundings. The use of digital technology in marketing has not been carried out optimally. In the implementation of this community service activity, the Asset Based Community Development (ABCD) method is used. Implementation of activities includes: Coordination with partners, Preparation, Socialization of Activity Materials and Instructors, Training and Mentoring. Based on the activities that have been carried out, it can be concluded that managerial marketing through social media has an important role in the MSME marketing process. The result of this socialization is that marketing manager can develop the marketing process so that it can maximize the latest technology